2021
DOI: 10.1007/s10557-020-07136-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Perivascular Adipose Tissue Function in Obesity Using Exercise

Abstract: Purpose Perivascular adipose tissue (PVAT) exerts an anti-contractile effect which is vital in regulating vascular tone. This effect is mediated via sympathetic nervous stimulation of PVAT by a mechanism which involves noradrenaline uptake through organic cation transporter 3 (OCT3) and β3-adrenoceptor-mediated adiponectin release. In obesity, autonomic dysfunction occurs, which may result in a loss of PVAT function and subsequent vascular disease. Accordingly, we have investigated abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 76 publications
(100 reference statements)
4
22
0
1
Order By: Relevance
“…Noradrenaline, which is the main SNS mediator, induces the expression of β3-adrenoreceptors, which are responsible for adiponectin release, while organic cation transporter 3 (OCT3) separates the excess of NA [38]. Saxton et al reported that obesity contributes to the downregulation of mentioned receptors among mice [123]. However, exercise performed on obese mice turned out to increase the expression of β3-adrenoreceptors and returned control levels of OCT3.…”
Section: The Influence Of Exercise Among Obese On Pvatmentioning
confidence: 99%
“…Noradrenaline, which is the main SNS mediator, induces the expression of β3-adrenoreceptors, which are responsible for adiponectin release, while organic cation transporter 3 (OCT3) separates the excess of NA [38]. Saxton et al reported that obesity contributes to the downregulation of mentioned receptors among mice [123]. However, exercise performed on obese mice turned out to increase the expression of β3-adrenoreceptors and returned control levels of OCT3.…”
Section: The Influence Of Exercise Among Obese On Pvatmentioning
confidence: 99%
“…Our results showed that aerobic exercise attenuates the hyperexcitation of sympathetic nerves in PVAT, represented by the reduced expression of circulating NE and the distribution of the sympathetic nerve. Exercise training has been shown to normalize sympathetic hyperexcitation in patients with HF [ 16 ], and to restore PVAT function and prevent vascular complications [ 21 ]. Quantitative evidence from HF patients systematically supported this positive influence of exercise [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a confirmed method for muscle mass maintenance in SCI or paralysis-bound patients who cannot actively contract muscles or who are at high risk of muscle atrophy. In this study, the non-obese group with less fat tissue interference [ 34 ] may have benefited more from FES for the contraction of paralyzed muscles than the obese group. In contrast to the muscle-related parameters, fat components including fat mass, fat percentage, and FMI increased during intervention regardless of obesity.…”
Section: Discussionmentioning
confidence: 99%